Managerial performance as influenced by entrepreneurial traits and mentoring attributes among academic department chairpersons - Causing, Virginia B. (Iloilo City West Visayas State University, 2001)
This descriptive-correlational study determined the influence of entreprenurial traits and mentoring attributes on the managerial performance of academic chairpersons in the institutions of higher learning in Iloilo City. Thirty-two (32) randomly selected academic department chairpersons responded to the three data gathering instruments -- the Entrepreneurial Rating Scale , the Mentor scale, and the Rating Scale on the Managerial performance of Academic Department Chairpersons of U.P. Los Banos. The third instrument was also fielded to the 200 randomly selected faculty members. Means, standard deviations, ranks, the t-test for independent samples, the One-Way Analysis of Variance, and the Stepwise Multiple Regression Analysis were employed in the analysis of the data gathered. Alpha level was set at .05. results revealed that, generally, the academic department chairpersons had "outstanding" managerial performance, had "average" entreprenuerial traits, "creativity", "drive and desire," and " confidence" were most dominant among them, while "independence" and "self-discipline" were least dominant. As to mentoring attributes, " sociability" and "openness' were likewise dominant among them, while " dominance" was least dominant. The academic department chairpersons did not differ significantly in their managerial performance, entreprenuerial traits, and mentoring attributes when grouped as to certain categories. Academic rank was a significant predictor of the academic department chairpersons' managerial performance. Highest educational attainment, number of years in present position, prior work experience, training in educational management, and academic rank were significant predictors of their entrepreneurial traits.
Dissertation (Ph.D.)--West Visayas State University, 2001.